Alfabetização científica nos anos iniciais: contribuições de uma sequência didática estruturada nos três momentos pedagógicos - Langaro, Raquel (2018)
The present research starts from the necessity to implement and analyze didactic proposals that favor the scientific literacy of the students since the initial years. The importance of promoting this scientific literacy in this stage of schooling dwells in the fact that it supports the construction of the first meanings about the world, expanding knowledge, culture and the possibility of understanding and effectively participating in society. With this perception, and accompanied by the understanding that teaching science is associated with seeking answers to the problems present in the near or remote surroundings of students, the question that guides research is formulated: What characteristics associated with scientific literacy are benefited by pedagogical practices based on the search for a solution to problems experienced by the students? In order to answer to this questioning, we search for the support of the methodological proposal developed by Delizoicov and Angotti (1991) named Three Pedagogical Moments -3PM based on the work of Paulo Freire. It takes a point of reference, the understanding of Scientific Literacy specifically in the understanding of Lorenzetti (2000). From these choices, it is inferred as the objective of the study, to evaluate a didactic sequence guided by the Three Pedagogical Moments to approach contents of Sciences in the initial years in terms of their contributions to the process of scientific literacy. For the development of the research, the study structures a didactic sequence, addressing the theme “Burns”. This didactic sequence is supported by 3PM and analyzes the contributions to scientific literacy. The research takes as presupposition the qualitative and participatory approach, involving the production of data from the teacher/researcher's records in the form of logbook, the collection of the materials elaborated by the students in the course of the meetings and the audio and video recording of one of the activities executed (television news). In this context, such analysis chooses as categories of analysis the characteristics pointed out by Lorenzetti (2000) as deriving from a pedagogical practice focused on scientific literacy in the early years. The results discussed in these categories indicate that the didactic sequence: was favorable to scientific literacy specifically in relation to the use of vocabulary enriched with scientific terms and concepts; to identify this knowledge in everyday situations; to identify that there are myths and beliefs in most of the knowledge acquired in the experiential world; about the conscious role that each subject must exercise in society; and their critical responsibility for the surrounding events. On the other hand, the didactic proposal elaborated has been weakened in aspects such as the identification that there is no absolute truth in science and that it is the fruit of a social, cultural, economic and political context.